Amino acid substitutions of acetylcholinesterase associated with carbofuran resistance in Chilo suppressalis1. Issue 12 (1st April 2014) - Chang, Cheng; Cheng, Xuan; Huang, Xin‐Yi; Dai, Shu‐Mei
Abstract BACKGROUND Over 1000‐fold carbofuran resistance has been observed in Chilo suppressalis (Walker) collected from the Changhua (CH) and Chiayi (CY) prefectures of Taiwan. An understanding of the pertinent mechanisms will benefit effective insecticide resistance management of C. suppressalis. RESULTS Among the five amino acid substitutions of acetylcholinesterase (AChE) identified in C. suppressalis, A314S and H668P had been reported and E101D, F402V and R667Q were novel. Substitution frequencies in AChE of CH and CY populations were much higher than in the susceptible Hsinchu (HC) population. Significantly negative correlations were observed between the frequencies of E101D, A314S and R667Q and the kinetic parameters of AChEs in these populations. AChE from the resistant CH population was less susceptible to the inhibition of carbofuran, with an I50 that was 3.6‐fold higher than that of the susceptible HC population. Although Km and Vmax of AChE from the CH and CY populations were reduced to 72–87% of those from the HC population, the overall catalytic efficiency (Vmax/Km) remained constant for all three populations. CONCLUSION Amino acid substitutions identified in the AChE of C. suppressalis are associated with changes in AChE kinetics and its insensitivity to carbofuran. These observations are helpful for rapid monitoring, prediction and management of OP and CB resistance in the field. © 2014 Society of Chemical Industry